Vegetation impact on the dune stability and formation on the Lithuanian coast of the Baltic sea - Urbonienė, Ramunė; Kelpšaitė, Loreta; Borisenko, Ingrida (Journal of Environmental Engineering and Landscape Management, 2015)
The aim of this study was to estimate vegetation coverage impact on the sandy beach and protective beach dune ridge (PBD) formation. Studies of the Lithuanian Baltic Sea coastal morphometric parameters and vegetation coverage projection were carried out from 1999 to 2011. In order to evaluate the dependence of the beach and the PBD morphometric parameters on the projection of vegetation coverage changes, correlation analyses were performed. A very strong link between vegetation projection coverage of the PBD top and beach width and incline of the eastern slope of PBD, and western slope vegetation projection coverage with the incline of the western slope of PBD were observed. A strong correlation relationship was observed between vegetation projection coverage of the PBD top and width of the PBD top. A medium relationship was noted between vegetation projection coverage of the PBD top with the width of the eastern slope. A negative relationship was noticed between the PBD western slope vegetation projection coverage and beach width. It may be admitted that the projection coverage of vegetation may be used as PBD’s parameter of stability as well as in the implementation of integrated coastal zone management.